Substance use disorder: above and beyond addiction - Kumar, Jaya; Mohamed, Wael Mohamed Yousef; Borroto-Escuela, Dasiel Oscar; Sangu, Muthuraju; Rashid, Rusdi; Mohamad Isa, Mohd Fadzli; Shanmugam, Prem Kumar (Frontiers Media SA, 2024)
Substance use disorder (SUD) has been, for an extended period, seen as a form of addiction and a chronic brain illness. The Research Topic “Substance use disorder: above and beyond addiction” adopts a wider perspective, delving into the multi-dimensional aspects of SUD and its numerous driving factors that result in its development, maintenance, and relapse, in addition to the management of the disease. We received a substantial number of submissions for this Research Topic, and 31 articles were finally published.